2018
DOI: 10.3920/jiff2017.0078
|View full text |Cite
|
Sign up to set email alerts
|

Performance of broiler chicks fed on two insect based-diets in South East Nigeria

Abstract: The performance of broiler chicks fed on two common species of edible insects: African palm larva (Rhynchophorus phoenicis) and winged termite (Macrotermes bellicosus) in south east, Nigeria were studied using 135 day old Arbor acre birds. Three dietary treatments (T1, T2 and T3) representing Diet A (control: vital feed based fishmeal), Diet B (African palm larvae meal; APLM), and Diet C (containing winged termite meal; WTM), respectively, were used. T1 comprised of a standard feed of brand name ‘vital feed’ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The performance of broiler chicks fed on two common edible insect species: APW and winged termite (Macrotermes bellicosus) was studied in southeast Nigeria. The results showed that broiler chicks fed with APW larvae meal had the highest records in all performance indices tested (weight gain, feed efficiency ratio, specific growth rate, protein efficiency ratio, and linear body measurements) (Amobi and Ebenebe, 2018a). In addition, under a similar procedure, APW feed can affect broiler chicken meat properties.…”
mentioning
confidence: 93%
“…The performance of broiler chicks fed on two common edible insect species: APW and winged termite (Macrotermes bellicosus) was studied in southeast Nigeria. The results showed that broiler chicks fed with APW larvae meal had the highest records in all performance indices tested (weight gain, feed efficiency ratio, specific growth rate, protein efficiency ratio, and linear body measurements) (Amobi and Ebenebe, 2018a). In addition, under a similar procedure, APW feed can affect broiler chicken meat properties.…”
mentioning
confidence: 93%
“…Winged termite is also ranked among the most preferred in Ebenebe et al (2017) even though it is seasonal; thus the interest of this study on these two species. Amobi and Ebenebe (2018) showed that broiler chicks fed on diets containing termites (Macrotermes bellicosus) and African palm weevil larvae (Rhyncophorus phoenicis) performed better in weight gain, feed efficiency, specific growth rate and linear body measurements compared to those control diets containing fishmeal.…”
Section: Introductionmentioning
confidence: 99%